2019
DOI: 10.3390/cells8010077
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Autophagy-Related Genes in the Pathogenesis of Inflammatory Bowel Disease

Abstract: Autophagy is an intracellular catabolic process that is essential for a variety of cellular responses. Due to its role in the maintenance of biological homeostasis in conditions of stress, dysregulation or disruption of autophagy may be linked to human diseases such as inflammatory bowel disease (IBD). IBD is a complicated inflammatory colitis disorder; Crohn’s disease and ulcerative colitis are the principal types. Genetic studies have shown the clinical relevance of several autophagy-related genes (ATGs) in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
72
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(74 citation statements)
references
References 178 publications
(242 reference statements)
0
72
0
2
Order By: Relevance
“…Autophagy was initially characterized as a nonspecific process induced under starvation conditions to recycle building blocks to compensate for the lack of nutrients, and thus was so-called nonselective bulk autophagy. Later, it has been evidenced that autophagy can be induced in non-starved cells to degrade specific substrates, such as aggregated proteins, damaged mitochondria or invading pathogens, which is known as selective autophagy [4]. Autophagy plays a key role in maintaining intestinal homeostasis, in regulating the interaction between gut microbiota and innate and adaptive immunity, and in host defense against intestinal pathogens [3].…”
Section: Introductionmentioning
confidence: 99%
“…Autophagy was initially characterized as a nonspecific process induced under starvation conditions to recycle building blocks to compensate for the lack of nutrients, and thus was so-called nonselective bulk autophagy. Later, it has been evidenced that autophagy can be induced in non-starved cells to degrade specific substrates, such as aggregated proteins, damaged mitochondria or invading pathogens, which is known as selective autophagy [4]. Autophagy plays a key role in maintaining intestinal homeostasis, in regulating the interaction between gut microbiota and innate and adaptive immunity, and in host defense against intestinal pathogens [3].…”
Section: Introductionmentioning
confidence: 99%
“…For example, among the genetic factors associated with the UC etiology, variants in the autophagy-related genes have been identified. Recent studies have shown that autophagy played a key role in maintaining intestinal homeostasis and regulating the interaction between gut microbiota and innate and adaptive immunity [ 16 , 17 ]. Therefore, the research progress of UC molecular mechanism based on microarray technology can provide potential targets for the diagnosis and treatment of UC.…”
Section: Discussionmentioning
confidence: 99%
“…This type of autophagy can be triggered by different stimuli, such as starvation, inflammation, oxidative stress, hypoxia, and toxic molecules. Studies have shown that dysregulation of autophagy is inextricably linked to the occurrence and development of CD[ 6 , 7 ]. Thus, in the present study, we used the Morris method to establish a rat model of CD and observed the effects of TNBS on colonic autophagy in rats.…”
Section: Discussionmentioning
confidence: 99%
“…Autophagy maintains intracellular homeostasis and promotes cell survival by decomposing related intracellular substrates[ 5 ]. Increasing evidence suggests that dysregulation of autophagy is inextricably linked to the onset of CD[ 6 , 11 ]. For example, autophagic dysfunction can reduce the restriction of intracellular replication of adherent-invasive E. coli (AIEC) and increase the secretion of proinflammatory factors such as tumor necrosis factor-α (TNF-α) and interleukin-6 (IL-6) in the intestine[ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%